Commodity Transport Studies Cement Planning Commission - Planning Commission (Planning Commission, 1966)
At the first meeting of the planning Committee for Transport held on July 2, 1963, it was decided that the Joint Technical Group should undertake, along with Other studies, the analysis of the present and future patterns of movement of selected commodities as part of a programme of technical and economic studies being undertaken to assist in the preparation of transport plan in out- airline for the period ending 1975-76 and in detail for the period of the Fourth Plan.
Joint Technical Group for Transport Planning, Planning Commission